Step-by-step explanation:
From the attached figure, OAB forms a triangle having,
a = (2,1)
b = (3,-2)
Vector, OA = 2x + y
Vector, AB = x - 3 y
The resultant can be calculated using triangular law of vector addition as :
![r=OA+AB](https://img.qammunity.org/2020/formulas/physics/high-school/v6lhd7z7j7a4cn7rnlhxxqztvnknvy1qtr.png)
![r=2x+y+(x-3y)](https://img.qammunity.org/2020/formulas/physics/high-school/vb346dmpolx4s00zd7jo1fbort3tz8eoh7.png)
![r=3x-2y](https://img.qammunity.org/2020/formulas/physics/high-school/6w4p2w7lc4q8a90gnwe9ig2n64hpfnoml6.png)
So, the sum of the vectors plotted below is
. Hence, the correct option is (c).